Multimedia University Cyberjaya / Ridhwan Ahmad Juanda - Ahmad Juanda, Ridhwan (UITM Cawangan Johor Kampus Pasir Gudang, 2014)
Industrial Training is a compulsory requirement for students in certain programs at all level higher education especially for university students. To increase the higher chance for graduate to able work, industrial program was introduced to strengthen their knowledge about the hardship of working from outside there. Industrial Training is making the student to learn the concept about working and also the level of opportunities that the student must grab fast. In the world, the competition of works is many and the student must receive the practical experience to know the reliability of market. Industrial Training concept is to make learning opportunities for the students is much easier and the open for job is simple to get. From this Industrial Training, the student will be able to practicing the skill and the development of working ethics and the quality of project that undertaken. The student also learns about the discipline of working that must be follows. The rules an the regulations of working are different types that must be punctuality. The student will be able to the mode of serious in the working. Students also will exhibit the pleasant interpersonal skills as an individual in working independently, collaborative and multifunction actions. Industrial Training will give a practice to students according to the organization skills in enhancing individual and group effectiveness and productivity. It is also exhibit the good communication among fellow workers and supervisors in issues that related to the project undertaken. Students of Diploma in Civil Engineering are required to undergo the industrial training at any constructions, consultants, developers or any other agencies that it is related to the civil engineering. These 2 months of industrial training is a part of education that the student must be parts. It has been held during the season break of semester holiday. The student of Diploma in Civil Engineering must be finish first of their semester 4 before there are taking the industrial training. During the last weeks of the industry training, students were supervised and monitored their company's respected supervisor from the faculty.